2013
DOI: 10.1371/journal.pone.0063991
|View full text |Cite
|
Sign up to set email alerts
|

Edible Crabs “Go West”: Migrations and Incubation Cycle of Cancer pagurus Revealed by Electronic Tags

Abstract: Crustaceans are key components of marine ecosystems which, like other exploited marine taxa, show seasonable patterns of distribution and activity, with consequences for their availability to capture by targeted fisheries. Despite concerns over the sustainability of crab fisheries worldwide, difficulties in observing crabs’ behaviour over their annual cycles, and the timings and durations of reproduction, remain poorly understood. From the release of 128 mature female edible crabs tagged with electronic data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Assuming they where predominantly females, these individuals could be migrating to suitable spawning grounds. Such migrations have been documented in several studies (Williamson, 1904;Meek, 1914;Bennett & Brown, 1983;Le Foll, 1986;Ungfors et al, 2007;Hunter et al, 2013). Tagging experiments of C. pagurus conducted by the Institute of Marine Science in the 1960's at Kjeldosen, just 40 km south of the location of our study, 8 demonstrated a primarily southward directional movement of mature female crabs in the area (Gundersen, 1977(Gundersen, , 1979.…”
Section: Discussionsupporting
confidence: 73%
“…Assuming they where predominantly females, these individuals could be migrating to suitable spawning grounds. Such migrations have been documented in several studies (Williamson, 1904;Meek, 1914;Bennett & Brown, 1983;Le Foll, 1986;Ungfors et al, 2007;Hunter et al, 2013). Tagging experiments of C. pagurus conducted by the Institute of Marine Science in the 1960's at Kjeldosen, just 40 km south of the location of our study, 8 demonstrated a primarily southward directional movement of mature female crabs in the area (Gundersen, 1977(Gundersen, , 1979.…”
Section: Discussionsupporting
confidence: 73%
“…Laboratory tests should be supplemented by field campaigns using biotelemetry and DSTs to document realised habitats by free-ranging animals (e.g. Hunter et al, 2013).…”
Section: Contentious Management Policies Imperil Conservation Aimsmentioning
confidence: 99%
“…In the North Sea, berried females migrate offshore to release larvae and then move back inshore to feed (Nichols et al, 1982). The time at which the crabs cease most activity is used as the onset of brooding and occurs from mid-November through to early January (Hunter et al, 2013). In the North Sea, egg development has been observed to cease in late November, at which point the eggs entered a period of diapause (Naylor et al, 1997).…”
Section: Reproduction and Juveniles 231 Matingmentioning
confidence: 99%
“…Spawning and larval development in C. pagurus are both dependent upon temperature and neither are triggered below 7 or 8ᵒC (Lindley, 1987). The pelagic larval stage lasts for approximately 3 months (Eaton et al, 2003, Hunter et al, 2013, Weiss et al, 2009 or at least for 60 days at temperatures of 15-20 ᵒC (Nichols et al, 1982). Larvae are detected in coastal waters from May until September.…”
Section: Pelagic Larval Stagementioning
confidence: 99%
See 1 more Smart Citation